A review of the health hazards of artificial sweeteners: are they safe? - Ebrahimzadeh Attari, Vahideh; Ardalan, Mohammad Reza; Malek Mahdavi, Aida; Gorbani, Abolfazl (Progress in Nutrition, 2018)
The increasing prevalence of obesity and diabetes mellitus has led to an increased production and consumption of artificially sweetened foods all over the world. Artificial sweeteners are high-intensity sweeteners which contribute no calorie. As a result, most of these foods may be sold with a “healthy” or “diet” labeling; however, there have been lots of controversy regarding their safety and adverse health effects. Therefore, the present article review aimed to summarize the results of most relevant studies concerning side effects of artificial sweeteners. Accordingly, a search of several databases was performed to identify all related manuscripts from 1980 to 2016. As a result, most of the available animal studies demonstrated that chronic exposure to artificial sweeteners led to increased body weight, impairment of glucose and insulin homeostasis, alteration in gut microbiota, neurobehavioral effects and also induction of kidney injury and cancer. However, the existing clinical and epidemiologic data are partly inconsistent to make a definitive conclusion regarding some of those adverse effects. In conclusion, consumers should be aware of the potential side effects of artificial sweeteners and it may be recommended that only minimal amounts of NNS could be consumed.